Opinion Piece Construction of R20 Forum on thejakartapost.com: Van Dijk's Model Critical Discourse Analysis - Nuraini, Herlyna; Pratama, Irham Yudha; Rosita, Ita; Ahnaf, Keyita (Anaphora : Journal of Language, Literary, and Cultural Studies, 2024)
Ideology flows through ideas or discourses, whether deliberate or not. This study aims to analyze the construction of an opinion piece entitled “R20, global change and transformation of religions” published by The Jakarta Post. Using the descriptive qualitative method, this study examines the structure of the text with the Critical Discourse Analysis model that Teun A. Van Dijk proposed. Van Dijk’s CDA model divided the text structure into three parts: macrostructure, superstructure, and microstructure. The result of the study explain that microstructure focused on the textual content of the whole news, superstructure discuss the integration and interrelationships between the subtopics contained in the discourse text, and the microstructure examines that the metaphor and idiomatic expressions aided the writer to get the message across. The finding shows mainly focus on the text structures and linguistic aspects observable in the text and what they imply. The analysis indicates that there is a connection between ideology and the language used in the discourse. By looking into the opinion piece and considering who wrote it, the purpose of the text becomes apparent. The article displays the ideology, as well as the social and political stance of the writer. Linguistic evidence shows the points that the writer emphasized in the discourse.